Cohort One 2023 Pitch Event and Field Visit Report - Niru, A.; Bohjanen, C.; Sewe, L. (International Livestock Research Institute, 2023)
The Food Systems Accelerator pitch event was held in Nairobi, Kenya on Thursday, the 26th of October 2023. The attendees included different capital providers, the 10 Accelerator Partners, the CGIAR scientists (technical assistance providers), the Ukama Ustawi leadership team and the implementation partners (IFDC-2SCALE and The Rallying Cry). The Accelerator Partners from Kenya, Rwanda, Uganda and Zambia, had the opportunity to pitch their businesses and compete for grant prizes following which, the first prize of $20,000 was awarded to Forest Africa Zambia Limited, the second prize of $18,000 to Yellow Star Produce and Food Processors (U) Ltd, and in third place was The Insectary, Kenya who were awarded $12,000. The other 7 Accelerator Partners were each awarded $10,000 for their consistent participation and efforts in the accelerator. The event, held at ILRI marked the close of the first cohort’s accelerator programme. The following day the Accelerator Partners and delivery partners conducted a field visit to Farm Works operations. During the field visit, the alumni network was launched.